Staphylococcus aureus Floating Biofilm Formation and Phenotype in Synovial Fluid Depends on Albumin, Fibrinogen, and Hyaluronic Acid - Knott, Samantha; Curry, Dylan; Zhao, Neil; Metgud, Pallavi; Dastgheyb, Sana S.; Purtill, Caroline; Harwood, Marc; Chen, Antonia F.; Schaer, Thomas P.; Otto, Michael; Hickok, Noreen J. (Frontiers in Microbiology, 2021)
Biofilms are typically studied in bacterial media which allow the study of important properties such as bacterial growth. However, the results obtained in such media cannot take into account the bacterial localization/clustering caused by bacterial-protein interactions in vivo and the accompanying alterations in phenotype, virulence factor production, and ultimately antibiotic tolerance. We and others have reported that methicillin-resistant or methicillin-sensitive S. aureus (MRSA or MSSA, respectively) and other pathogens assemble a proteinaceous matrix in synovial fluid. This proteinaceous bacterial aggregate is coated by a polysaccharide matrix as is characteristic of biofilms. In this study, we identify proteins important for this aggregation and determine the concentration ranges of these proteins that can reproduce bacterial aggregation. We then test this protein combination for its ability to cause marked aggregation, antibacterial tolerance, preservation of morphology, and expression of the phenol-soluble modulin (PSM) virulence factors. In the process, we create a viscous fluid that models bacterial behavior in synovial fluid. We suggest that our findings and, by extension, use of this fluid, can help to better model bacterial behavior of new antimicrobial therapies, as well as serve as a starting point to study host protein-bacterial interactions characteristic of physiological fluids.